2013
DOI: 10.1080/17470218.2013.863371
|View full text |Cite
|
Sign up to set email alerts
|

The Life of p: “Just Significant” Results are on the Rise

Abstract: Null hypothesis significance testing uses the seemingly arbitrary probability of .05 as a means of objectively determining whether a tested effect is reliable. Within recent psychological articles, research has found an overrepresentation of p values around this cut-off. The present study examined whether this overrepresentation is a product of recent pressure to publish or whether it has existed throughout psychological research. Articles published in 1965 and 2005 from two prominent psychology journals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 19 publications
1
87
11
Order By: Relevance
“…Bakker and Wicherts (2011) found that 50% of the articles reporting the results of NHST tests in the psychological literature contained at least one such inconsistent p-value, and that 18% of the statistical results was incorrectly reported. Similar yet slightly lower error rates have been found in the medical literature (Berle & Starcevic, 2007;Garcia-Berthou & Alcaraz, 2004) and in recent replications (Bakker & Wicherts, 2014a;Caperos & Pardo, 2013;Leggett, Thomas, Loetscher, & Nicholls, 2013). Bakker and Wicherts (2011) discuss different reasons why these inconsistent p-values may appear.…”
Section: Statistical Reporting Errors and Collaboration On Statisticasupporting
confidence: 71%
See 1 more Smart Citation
“…Bakker and Wicherts (2011) found that 50% of the articles reporting the results of NHST tests in the psychological literature contained at least one such inconsistent p-value, and that 18% of the statistical results was incorrectly reported. Similar yet slightly lower error rates have been found in the medical literature (Berle & Starcevic, 2007;Garcia-Berthou & Alcaraz, 2004) and in recent replications (Bakker & Wicherts, 2014a;Caperos & Pardo, 2013;Leggett, Thomas, Loetscher, & Nicholls, 2013). Bakker and Wicherts (2011) discuss different reasons why these inconsistent p-values may appear.…”
Section: Statistical Reporting Errors and Collaboration On Statisticasupporting
confidence: 71%
“…We estimated the prevalence of inconsistent p-values in six top psychology journals by means of an automated procedure to retrieve and check errors in the reporting of statistical results, in order to replicate earlier estimates of error rates in the psychological literature Bakker & Wicherts, 2014a;Caperos & Pardo, 2013;Leggett et al, 2013). Our results show a somewhat higher probability for articles to contain at least one p-value that comprises an error compared to the two studies by Bakker and Wicherts (63% vs. 45% (2014a) and 50% (2011)), and a higher probability for articles to contain at least one p-value that comprises a gross error (20% vs. 15% (2011; 2014a)).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a psychologist's admission to a QRP that is less often admitted to by others usually implies his or her admission to QRPs with a higher admission rate in the entire sample. Given that rounding down p-values close to .05 was one of the QRPs with relatively low admission rates, the frequency of misreported p- Previous research found a decrease in negative results (Fanelli, 2012) and an increase in reporting inconsistencies (Leggett, Thomas, Loetscher, & Nicholls, 2013) suggesting that QRPs are on the rise. On the other hand, it has been found that the number of published corrections to the literature did not change over time, suggesting no change in QRPs over time (Fanelli, 2013(Fanelli, , 2014.…”
Section: Most Conclusion In Psychology Are Based On the Results Of Nmentioning
confidence: 99%
“…Leggett et al (2013) recently studied reporting errors in two main psychology journals in 1965 and 2005. They found that the increase in reporting inconsistencies over the years was higher in the Journal of Personality and Social Psychology (JPSP), the flagship journal of social psychology, than in Journal of…”
Section: Most Conclusion In Psychology Are Based On the Results Of Nmentioning
confidence: 99%
“…"(Aitkenhead, 2013) P-hacking is the practise of getting the results required regardless of the data by means of academic misconduct and rigged statistical testing. The mildest forms of p-hacking, from the author's personal experiences and others', are extremely widespread (Head et al, 2015;Lakens, 2015;Leggett et al, 2013;Masicampo and Lalande, 2012). This brings us to the crux of the present problems.…”
Section: Science Hackingmentioning
confidence: 96%